Digitalisation in Europe 2021-2022 Evidence from the EIB Investment Survey - European Investment Bank (2022)
"The coronavirus crisis accelerated the digital transformation of Europe's economy. Before the pandemic, cutting-edge digital technologies were primarily used by the most innovative and modern firms. The COVID-19 crisis, however, brought the digital transformation to the larger society - and made digitalisation integral to firms' survival. Digital firms were better able to cope with the disruption unleashed by the pandemic, and they were less likely than non-digital firms to see sales decline significantly from 2020 onwards. Many of them used the crisis an opportunity to accelerate their digitalisation. The Digitalisation in Europe 2021-2022 report uses results from the EIB Investment Survey (EIBIS), conducted from April to July 2021, to shed light on the level of digitalisation among Europe's small and medium firms."